2007
DOI: 10.1098/rspb.2007.0687
|View full text |Cite
|
Sign up to set email alerts
|

Parental prey selection affects risk-taking behaviour and spatial learning in avian offspring

Abstract: Early nutrition shapes life history. Parents should, therefore, provide a diet that will optimize the nutrient intake of their offspring. In a number of passerines, there is an often observed, but unexplained, peak in spider provisioning during chick development. We show that the proportion of spiders in the diet of nestling blue tits, Cyanistes caeruleus, varies significantly with the age of chicks but is unrelated to the timing of breeding or spider availability. Moreover, this parental prey selection suppli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
116
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(123 citation statements)
references
References 27 publications
4
116
0
Order By: Relevance
“…We believe that this type of basic information is needed before we can answer more sophisticated questions, such as, would global warming lead to diet shifts in these species (Both, 2010)? Lastly, as in previous studies (Arnold et al, 2007), the relationship between spider intake and nestling size shown here highlights the importance of considering not only the composition of nestling food, but also the quality of the diet (its nutritional value) and the influence of this factor on offspring growth and development.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…We believe that this type of basic information is needed before we can answer more sophisticated questions, such as, would global warming lead to diet shifts in these species (Both, 2010)? Lastly, as in previous studies (Arnold et al, 2007), the relationship between spider intake and nestling size shown here highlights the importance of considering not only the composition of nestling food, but also the quality of the diet (its nutritional value) and the influence of this factor on offspring growth and development.…”
Section: Discussionmentioning
confidence: 80%
“…More recent studies (Ramsay & Houston, 2003) have shown that spiders are nutritionally similar to caterpillars, except that spiders contain high levels of taurine, an amino acid essential for the proper development and function of the central nervous system (Ramsay & Houston, 2003;Arnold et al, 2007 and references therein). Taurine is also reported to have effects on personality (e.g., risk-taking behaviour) and cognition in offspring (Arnold et al, 2007). To our knowledge, no studies have shown a direct link between taurine levels and body size in wild birds, despite there being some evidence from poultry that taurine is a growth factor directly associated with bone growth (Martin & Patrick, 1961).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Fledging mass was also not linked to PSP, suggesting that food availability during the nestling stage as such was not the driving factor. Arnold et al [128] reported a link between the availability of an important amino acid found in spiders and cognitive development in the blue tit (Cyanistes caeruleus). Given that invertebrate density in general is higher in oak-rich habitats and is also likely to be higher where competition is less pronounced in low population density, our results on individual differences in PSP could instead be best explained by dietary composition during early nestling development.…”
Section: (Iii) Nestling Environmentmentioning
confidence: 99%
“…It is not only the amount of food, but the type of diet that matters. For example, blue tit (Cyanistes caeruleus) nestlings supplemented with taurine (an amino acid important for early development) performed better as adults in a spatial memory task compared with taurine-deprived blue tits (Arnold et al, 2007). However, other studies in rats (Rattus norvegicus) have found the opposite result.…”
Section: Introductionmentioning
confidence: 51%